Banana Tree Midrip Sap as an Antibacterial Staphylococcus aureus in Preventing Infection on External Wounds - Intan Nur Aini; Dzafera Noor Muchlisha; I Wayan Ari Adinata; Nur Halimah; Rifa Nur Afifah Farhat; Yuliana Salman (Jurnal Media Analis Kesehatan, 2023)
Wounds are damage to tissue continuity due to trauma from sharp or blunt objects, changes in temperature, chemistry, electricity, radiation, or animal bites. Wounds that are not handled properly can easily become infected, which can be caused by bacteria, one of which is Staphylococcus aureus. This study aims to determine the effectiveness of banana tree midrib sap as an antibacterial Staphylococcus aureus in preventing infection in external wounds. The research design used was experimental with a Completely Randomized Design (CRD) with a post test only control group design pattern. The research samples consisted of kepok banana tree midrib sap and Staphylococcus aureus bacterial culture using an accidental sampling technique. The antibacterial test method uses the well method by measuring the diameter of the clear zone on the media. The data collected was analyzed statistically using the Kruskal Wallis test and continued with the Post Hoc Kruskal Wallis test with a confidence level of 95%. The results showed that the sap of the banana tree midrib showed an influence on the Staphylococcus aureus bacteria with a value of sig. 0.01 (α<0.05). Banana tree sap (Musa Paradisiaca L) has an effect at concentrations of 15%, 30% and 60% on Staphylococcus aureus bacteria. These results are in accordance with the results of the qualitative phytochemical test of Kepok banana tree midrib sap which contains alkaloids, saponins, flavonoids and tannins which function as antibacterials. The conclusion of this research is that banana tree midrib sap has great potential as an antibacterial for Staphylocoocus aureus in preventing infections in external wounds